Analisis Strategi Mempertahankan Nilai, Kepuasan Dan Loyalitas Pelanggan Lampu Hannochs Terhadap Disributor Hannochs Di Tembung - Arsyrah Fitri; Teresia Bunga; Andika Sihotang; Lenti Susanna Saragih (Student Scientific Creativity Journal, 2023)
This research aims to determine strategies for maintaining customer value, satisfaction and loyalty towards Hannochs brand lamps carried out by several Hannochs distributors in Tembung. The sampling technique used was purposive sampling with Hannochs customers at one of the Hannochs distributor shops in Tembung. Data collection methods are participatory observation and interviews. The results of the research show that consumer loyalty, consumer satisfaction with the quality of Hannochs lighting products are met with durability, product guarantees and various product variations so that consumer needs and desires are met, in several shops the service quality of Hannochs distributor shops also meets customer satisfaction with friendly service, respond quickly, and help resolve consumer problems in using the product.